2013
DOI: 10.11607/jomi.2442
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Stress Distribution with Splinted and Nonsplinted Maxillary Anterior Fixed Prostheses Supported by Zirconia or Titanium Implants

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…Regarding the union factor, the main results pointed to the beneficial effect of the splinting technique in reducing tensions around the periimplant region, which is consistent with the literature [4,7,23,24]. This is especially true of Guichet et al [6] and Menani et al [25] who, in a photo-elastic test, found similar results to our study, with regard to the pattern of stress distribution for implants with splinted crowns compared to single unit crowns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the union factor, the main results pointed to the beneficial effect of the splinting technique in reducing tensions around the periimplant region, which is consistent with the literature [4,7,23,24]. This is especially true of Guichet et al [6] and Menani et al [25] who, in a photo-elastic test, found similar results to our study, with regard to the pattern of stress distribution for implants with splinted crowns compared to single unit crowns.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the literature presents no consensus on the advantage of the concept of splinting for implant-supported prostheses. Different methodologies are used to evaluate the biomechanical behavior of implants, which include: extensometry [3], tri-dimensional finite [4], and photo-elastic elements [5]. Among them, Yang et al [3] observed no significant differences in the distribution of the stress generated between the single unit and splinted implant prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…This result can be explained by the elastic characteristics of the fabrication material; for the same load and implant design, a more rigid implant absorbs more stress. Similar results were obtained by Çaglar et al in their analysis of finite element comparing zircon and titanium implants [33–35]. These results also correspond to the results of Osman et al who analyzed a denture model and, in comparing the two materials, found similar results but with smaller differences in the two materials [36], likely because the design of the prosthesis was different from the one studied here and from the designs in the previously cited studies.…”
Section: Discussionsupporting
confidence: 90%
“…The application of repeated loads can lead to fatigue failure of the interface, decreasing peri-implant bone density, and leading to the formation of bone defects 22 . Regarding the stress distribution in bone and implant, the stress peak concentration was located at the screw, cortical bone and implant neck area on implant/abutment interface, both for the vertical and oblique forces 23 . This study confirms our results, in which higher stress peak concentration was located at the cortical bone, screw and implant neck area on models with an external hexagon dental implant.…”
Section: Discussionmentioning
confidence: 99%